A WEB BASED SYSTEM FOR ONLINE STUDENT TRANSACTION AMONG SULAIMANIYAH CITY SCHOOL APPLICATION - Roshna Muhamad M. Amin; Miran Hikmat Mohammed Baban (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Nowadays, many schools provide a different level of education for their students. The objective is to change the place of the school where the students study and change it to another college in different place. However, it is obvious that in Kurdistan Iraqi region, any documentation related to education process will need to go through the Ministry of education, and this process takes a lot of time because of the distance between the offices in the city. Some paper works need to be done in order to accomplish any kind of task related to education processing including student transition among the schools and colleges either inside the city itself or in the city border such as towns and villages. It also takes a lot of time. This research tries to find out the newest methodology in Kurdistan cities that leads to provide a transformation of the old and classical system to computerized system, which can help the education sector over all the Kurdistan cities to become electronic. This can be done by providing online web pages to perform all these tasks. In addition, this kind of system will be considered as the first system for the Sulaimaniyah education center including all the schools in the cities. These changes may reduce the amount of possible traffic on the streets, as well as huge load on the organizations in education sector. Here student data can also be archived for the future use.